2006
DOI: 10.1590/s1516-89132006000600013
|View full text |Cite
|
Sign up to set email alerts
|

Floristic and phytosociological description of a riparian forest and the relationship with the edaphic environment in Caiuá Ecological Station - Paraná - Brazil

Abstract: Relationship in soil physical and chemical properties of soil, floristic and phytosociological association of semideciduous riparian forest of the Paranapanema River (R) and Rosana Reservoir (Re)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
(17 reference statements)
2
2
0
7
Order By: Relevance
“…2) have yielded results consistent with those we obtained for the FSM, the index we obtained for the INP was lower than those reported in all of the studies we reviewed. The same pattern was observed for the evenness index for the INP, which was lower in the present study than in other studies, whereas the evenness index for the FSM was consistent with those of the same studies (Ivanauskas et al 1999;Bianchini et al 2003;Jurinitz & Jarenkov 2003;Silva et al 2004;Costa-Filho et al 2006;Prado-Júnior et al 2011). Connell (1978) proposed that higher species diversity is maintained under intermediate levels of disturbance.…”
Section: Discussionsupporting
confidence: 92%
“…2) have yielded results consistent with those we obtained for the FSM, the index we obtained for the INP was lower than those reported in all of the studies we reviewed. The same pattern was observed for the evenness index for the INP, which was lower in the present study than in other studies, whereas the evenness index for the FSM was consistent with those of the same studies (Ivanauskas et al 1999;Bianchini et al 2003;Jurinitz & Jarenkov 2003;Silva et al 2004;Costa-Filho et al 2006;Prado-Júnior et al 2011). Connell (1978) proposed that higher species diversity is maintained under intermediate levels of disturbance.…”
Section: Discussionsupporting
confidence: 92%
“…Also in the upper region of the diagram, C. americana, L. nitidus and M. stipitatum were associated with high humidity in SSF Submontana regions, which were also observed by Scipioni et al (2013) in an Alluvial Submontana FED. Costa et al (2006) found high densities of B. densiflora in a Fluvic Neossol, corroborating the distribution of this species in the Park.…”
Section: Discussionsupporting
confidence: 76%
“…Del Quiqui et al (2007) also found in a plateau of SSF Submontana, in the north of Paraná, H. balansae and A. polyneuron. Costa et al (2006), in turn, cited A. polyneuron and B. riedelianum under the same environmental conditions. M. frondosus also appears in the upper portion of the diagram, slightly to the right due to the higher occurrence in the intermediate altitude regions (450 to 650 m).…”
Section: Discussionmentioning
confidence: 93%
“…O elevado valor de importância apresentado por Calophyllum brasiliense se deveu à presença de indivíduos de grande porte, resultando em altos valores de dominância. Há estudos em que a espécie foi uma das de maior valor de importância em ambientes de restinga não inundável (Guedes et al, 2006) ou em áreas ripárias de Floresta Estacional Semidecidual (Toniato et al, 1998;Costa Filho et al, 2006;OliveiraFilho et al, 1994) ou mesmo em caxetais (Galvão et al, 2002), em razão, justamente, da sua dominância.…”
Section: Processamento De Dadosunclassified